Maximum Power Point Tracking (MPPT) Pada Sistem Pembangkit Listrik Tenaga Angin Menggunakan Buck-Boost Converter - Muhamad Otong; Rifai Mardanie Bajuri (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2016)
In this paper, the implementation of the Maximum Power Point Tracking (MPPT) technique is developed using buck-boost converter. Perturb and observe (P&O) MPPT algorithm is used to searching maximum power from the wind power plant for charging of the battery. The model used in this study is the Variable Speed Wind Turbine (VSWT) with a Permanent Magnet Synchronous Generator (PMSG). Analysis, design, and modeling of wind energy conversion system has done using MATLAB/simulink. The simulation results show that the proposed MPPT produce a higher output power than the system without MPPT. The average efficiency that can be achieved by the proposed system to transfer the maximum power into battery is 90.56%.